Microfluidics with fluid walls. Issue 1 (December 2017) - Walsh, Edmond; Feuerborn, Alexander; Wheeler, James; Tan, Ann; Durham, William; Foster, Kevin; Cook, Peter
Abstract Microfluidics has great potential, but the complexity of fabricating and operating devices has limited its use. Here we describe a method — Freestyle Fluidics — that overcomes many key limitations. In this method, liquids are confined by fluid (not solid) walls. Aqueous circuits with any 2D shape are printed in seconds on plastic or glass Petri dishes; then, interfacial forces pin liquids to substrates, and overlaying an immiscible liquid prevents evaporation. Confining fluid walls are pliant and resilient; they self-heal when liquids are pipetted through them. We drive flow through a wide range of circuits passively by manipulating surface tension and hydrostatic pressure, and actively using external pumps. Finally, we validate the technology with two challenging applications — triggering an inflammatory response in human cells and chemotaxis in bacterial biofilms. This approach provides a powerful and versatile alternative to traditional microfluidics. The complexity of fabricating and operating microfluidic devices limits their use. Walsh et al. describe a method in which circuits are printed as quickly and simply as writing with a pen, and liquids in them are confined by fluid instead of solid walls.